EFFECT OF PROCESSES OF TRANSITION ON THE IMPOVERISHMENT OF RURAL SETTLEMENTS AND AGRICULTURE - Живковић, Драгић; Јелић, Сретен; Рајић, Зоран; Пешевски, Миле (Economics of Agriculture, 2011)
Globalization, situated in the modern era, refers to the increasing unifcation of world's economic, political, geostrategic and other vital activities benefting primarily developed countries and impoverishing underdeveloped countries and those already poor, ignoring at the same time all aspects of humanity. In our country, the process of globalization was preceded by transitional reforms especially in agriculture. Unfortunately, so far no positive results have been recorded as reforms were usually lagging behind and mostly ineffcient (promt import liberalization). Effcient and synchronized transitional reforms including denationalization are needed having clearly defned goals of the adopted strategy and policy measures.